How much are we willing to pay to send poor adolescents to school? Simulating changes to Mexico's Oportunidades in urban areas - Viviane Azevedo; César P. Bouillon; Patricia Yá\~nez-Pagans (Inter-American Development Bank, Research Department, 2009)
Although Mexico's Conditional Cash Transfer Program Oportunidades has increased overall school enrollment, many adolescents do not attend school, especially in urban areas. This paper simulates the effects of changes in program design using a simple parametric method based on a simultaneous probability model of school attendance and child labor. The paper also provides alternative non parametric simulation results by extending Todd and Wolpin's (2006) method to incorporate changes in working hours when attending school. The results indicate that eliminating or reducing school subsidies for primary education and increasing transfer for older students is a cost-effective way to raise overall school enrollment in urban areas. Increasing school attendance of 16-year-olds to 80 percent or more, however would require a quadrupling of scholarships. This suggests that complementary interventions are needed.
Keywords: I20; J22; 330; School attendance and work; Conditional cash transfers; Simulation; Oportunidades